1999
DOI: 10.1115/1.533734
|View full text |Cite
|
Sign up to set email alerts
|

A Contribution on Quasi-Static Mooring Line Damping

Abstract: Since the pioneering work of Huse (1986, “Influence of Mooring Line Damping Upon Rig Motions,” Proc., 18th OTC Conference), it is well known that mooring lines may account for a large fraction of the overall damping present in a moored floating structure. This paper is concerned with the mooring line damping induced by the low-frequency, quasi-static, horizontal motion of the mooring line fairlead. The main advantage of the quasi-static approach is that it is much faster than the more accurate finite element m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Most of the works are based on estimations of energy dissipation by the quasi-static method (Huse and Matsumoto, 1988, Liu and Bergdahl, 1998, Bauduin and Naciri, 2000 or the dynamic method (Huse and Matsumoto, 1989, Webster, 1995, Brown and Mavrakos, 1999. Most of the works are based on estimations of energy dissipation by the quasi-static method (Huse and Matsumoto, 1988, Liu and Bergdahl, 1998, Bauduin and Naciri, 2000 or the dynamic method (Huse and Matsumoto, 1989, Webster, 1995, Brown and Mavrakos, 1999.…”
Section: Damping Of Mooringsmentioning
confidence: 99%
“…Most of the works are based on estimations of energy dissipation by the quasi-static method (Huse and Matsumoto, 1988, Liu and Bergdahl, 1998, Bauduin and Naciri, 2000 or the dynamic method (Huse and Matsumoto, 1989, Webster, 1995, Brown and Mavrakos, 1999. Most of the works are based on estimations of energy dissipation by the quasi-static method (Huse and Matsumoto, 1988, Liu and Bergdahl, 1998, Bauduin and Naciri, 2000 or the dynamic method (Huse and Matsumoto, 1989, Webster, 1995, Brown and Mavrakos, 1999.…”
Section: Damping Of Mooringsmentioning
confidence: 99%
“…Hydrodynamic drag and friction damping are significantly affected by the motion of a floating platform aside from the internal damping caused by material properties. Many studies investigated the contribution of mooring line damping to the global responses of a deepwater floating platform, such as the quasistatic model series of mooring damping calculation [ 16 19 ]. Webster [ 20 ] used a time domain finite element approach for the parametric study of mooring line damping induced by both horizontal and vertical top end oscillations, and the parameters used in this analysis step from a dimensional analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The mooring force on the WEC therefore consists only of the position dependent static restoring force, shown for example in Figure 8. Implementation of quasi-static models for offshore mooring applications, and a review of their development, can be found in [72,84,94,95] and, for the specific case of wave energy applications, in Nava et al [96].…”
Section: Quasi-static Modelsmentioning
confidence: 99%
“…Huse [70] had previously proposed that drag forces, due to the motion of the mooring lines through the water, were the main source of energy dissipation, the reason being that a small offset of the top end can result in large transverse displacements along the mooring line ( Figure 6), inducing considerable drag forces. A number of other authors, such as Liu [71], Bauduin and Naciri [72], and Lie et al [73], have built upon the early work of Huse [69,70], to improve the modelling of mooring line-induced damping.…”
Section: Resistancementioning
confidence: 99%
See 1 more Smart Citation